Memahami Peran Hak Angket Dewan Perwakilan Rakyat dalam Pemilu: Perspektif Hukum Positif dan Fikih Siyasah - Rosalima, Fahrica; Asrudi, Asrudi (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
The inquiry right of the people's representative council is a situation where the right used by the DPR is to understand the state of the government, both in terms of knowing the implementation of governance and to seek materials to formulate a policy, or to provide approval or consideration regarding the possibilities of all government performance, which is also in line with the duties of the majelis syura in Islamic governance. The right of inquiry also plays a significant role in the successful conduct of elections; therefore, this paper will explain the role of the DPR's right of inquiry in elections from the perspective of positive law and fiqh siyasah. The research method used in this work is library research. (library research). From the analysis conducted, the role of the DPR's inquiry rights in elections from the perspective of positive law and fiqh siyasah has similarities in its duties and functions. Therefore, the results of this research are expected to provide understanding and knowledge about the role of the DPR's inquiry rights in elections from the perspective of positive law and fiqh siyasah.